Towards the Use of Lichens as a Source of Bioactive Substances for Topical Applications - Izabela Baczewska; Barbara Hawrylak-Nowak; Martyna Zagórska-Dziok; Aleksandra Ziemlewska; Zofia Nizioł-Łukaszewska; Grzegorz Borowski; Sławomir Dresler (Molecules, 2024)
The increasing incidence of dermatological diseases prompts the search for new natural methods of treatments, and lichens, with their special symbiotic structure, are a little-known and promising source of biologically active substances. Seven lichen species, Cladonia unicialis (L.) Weber ex F.H. Wigg. (Cladoniaceae), Evernia prunastri (L.) Ach. (Parmeliaceae), Hypogymnia physodes (L.) Nyl. (Parmaliaceae), Parmelia sulcata (Taylor) (Parmeliaceae), Physcia adscendens (Fr.) H. Olivier (Physciaceae), Pseudoevernia furfuracea (L.) Zopf (Parmeliaceae), and Xanthoria parietina (L.) Th. Fr. (Teloschistaceae), were used in our experiment. We identified different metabolites in the acetone extracts of all the lichen species. Based on the high-performance liquid chromatography analysis, the content of lichen substances in the extracts was evaluated. The impact of the individual lichen-specific reference substances, compared to the lichen extracts, on the viability of keratinocytes (HaCaT cell line) and fibroblasts (BJ cell line) and on the activity of selected skin-related enzymes was investigated. Our results revealed that only emodin anthrone at a concentration of 200 mg/L was cytotoxic to keratinocytes and fibroblasts in both cell viability assays. In turn, the C. uncialis extract was only cytotoxic to keratinocytes when used at the same concentration. The other tested treatments showed a positive effect on cell viability and no cytotoxicity or indeterminate cytotoxicity (shown in only one of the tests). Elastase and collagenase activities were inhibited by most of the lichen extracts. In turn, the individual lichen compounds (with the exception of evernic acid) generally had an undesirable stimulatory effect on hyaluronidase and collagenase activity. In addition, almost all the tested compounds and extracts showed anti-inflammatory activity. This suggests that some lichen compounds hold promise as potential ingredients in dermatological and skincare products, but their safety and efficacy require further study. The high cytotoxicity of emodin anthrone highlights its potential use in the treatment of hyperproliferative skin diseases such as psoriasis.